Transductive 3D Shape Segmentation using Sparse Reconstruction - Xu, Weiwei; Shi, Zhouxu; Xu, Mingliang; Zhou, Kun; Wang, Jingdong; Zhou, Bin; Wang, Jinrong; Yuan, Zhenming (Computer graphics forum, 2014)
We propose a transductive shape segmentation algorithm, which can transfer prior segmentation results in database to new shapes without explicitly specification of prior category information. Our method first partitions an input shape into a set of segmentations as a data preparation, and then a linear integer programming algorithm is used to select segments from them to form the final optimal segmentation. The key idea is to maximize the segment similarity between the segments in the input shape and the segments in database, where the segment similarity is computed through sparse reconstruction error. The segment‐level similarity enables to handle a large amount of shapes with significant topology or shape variations with a small set of segmented example shapes. Experimental results show that our algorithm can generate high quality segmentation and semantic labeling results in the Princeton segmentation benchmark.